Bare bones a survey of forensic anthropology - Warren, Michael W.; Parr, Nicolette M.; Zambrano, Carlos J.; Skorpinski, Katherine E. (Kendall Hunt, 2011)
Update of 2008 edition with minor corrections and more photographic examples.